High-dose testosterone treatment reduces monoamine oxidase A levels in the human brain: A preliminary report. (November 2021) - Kranz, Georg S.; Spies, Marie; Vraka, Chrysoula; Kaufmann, Ulrike; Klebermass, Eva-Maria; Handschuh, Patricia A.; Ozenil, Marius; Murgaš, Matej; Pichler, Verena; Rischka, Lucas; Nics, Lukas; Konadu, Melisande E.; et al.
Abstract: The sex hormones testosterone and estradiol influence brain structure and function and are implicated in the pathogenesis, prevalence and disease course of major depression. Recent research employing gender-affirming hormone treatment (GHT) of gender dysphoric individuals and utilizing positron emission tomography (PET) indicates increased serotonin transporter binding upon high-dosages of testosterone treatment. Here, we investigated the effects of GHT on levels of monoamine oxidase A (MAO-A), another key target of antidepressant treatment. Participants underwent PET with the radioligand [ 11 C]harmine to assess cerebral MAO-A distribution volumes (VT ) before and four months after initiation of GHT. By the time this study was terminated for technical reasons, 18 transgender individuals undergoing GHT (11 transmen, TM and 7 transwomen, TW) and 17 cis-gender subjects had been assessed. Preliminary analysis of available data revealed statistically significant MAO-A VT reductions in TM under testosterone treatment in six of twelve a priori defined regions of interest (middle frontal cortex (−10%), anterior cingulate cortex (−9%), medial cingulate cortex (−10.5%), insula (−8%), amygdala (−9%) and hippocampus (−8.5%, all p<0.05)). MAO-A VT did not change in TW receiving estrogen treatment. Despite the limited sample size, pronounced MAO-A VT reduction could be observed, pointing towards a potential effect of testosterone. Considering MAO-A's central role in regulation of serotonergic neurotransmission, changes to MAO-A VT should be further investigated as a possible mechanism by which testosterone mediates risk for, symptomatology of, and treatment response in affective disorders. Highlights: Gender-affirming hormone treatment (GHT) allows assessment of high-dose cross-sex hormone effects. Here we assess effects of GHT on brain MAO-A, previously shown as increased in depression. MAO-A was downregulated under testosterone treatment in female to male individuals. Observed effects are a human in vivo confirmation of previous animal data. Future studies should explore MAO-A as a potential correlate for testosterone's antidepressant properties.